Unlocking Excellence: Khageri Irrigation System Benchmarking in Chitwan - Shrestha, Neshan; Awasthi, Keshab Datt; Bohara, Niraj (Journal of UTEC Engineering Management, 2024)
DOI: https://doi.org/10.36344/utecem.2024.v02i01.007 The objective of the study was to assess the present service delivery, financial and productivity indicators. The performance of five branch canals i.e. Branch Canal 1, Branch Canal 4, Branch Canal 6, Branch Canal 7 and Branch Canal 8 of the Khageri Irrigation System was evaluated for 2023 AD using fifteen performance indicators under water supply, financial performance and agricultural productivity categories suggested by the International Programme for Technology and Research in Irrigation and Drainage (IPTRID). 331 farmers were interviewed in respective five branch canals from head, middle, and tail portions of the command area in order to get a representative sample. The data obtained from the interview was analysed and interpreted to calculate the values of the performance indicators. It was also found that the canal capacity and scheme infrastructure was not the limiting cause of this observation according to the calculation of water delivery capacity (1.08). The irrigation service fee charged was not sufficient to pay for the Operation and Maintenance (O&M) cost according to the calculation of revenue collection performance (0.5, 50%). Land productivity in this system was found to be unsatisfactory according to the calculations of output per unit command area (13084.76 Rs/ha), ouput per unit irrigated area (13216.93 Rs/ha) and output per unit irrigation supply (1.82 Rs/m3).